Course of pattern-reversed visual evoked cortical potentials in 30 eyes after bony orbital decompression in dysthyroid optic neuropathy. Issue 2 (28th June 2010) - Lipski, A; Eckstein, A; Esser, J; Loesch, C; Mann, K; Mohr, C; Jurklies, B
Abstract : Aim: To investigate optic nerve function using the pattern-reversed visual evoked cortical potentials (VECP) before and after bony orbital decompression in dysthyroid optic neuropathy (DON) due to Graves' disease. Methods: A total of 30 eyes of 15 patients (n=14 female) were observed over 30±13 months after bony three-wall orbital decompression. We examined visual acuity (VA), VECP P100 amplitudes and latencies, as well as proptosis using Hertel's exophthalmometry. Results: Mean logarithm of the minimum angle of resolution (logMAR) VA increased, statistically significantly, by 2.4 lines during 30±13 months (from 0.38±0.25 before surgery to 0.14±0.1 at the end of observation, p=0.0001). All eyes maintained or improved vision by at least one line. Mean postoperative reduction of proptosis was 6.4±3 mm. While VECP P100 amplitudes improved significantly, P100 latencies remained abnormal in 18 eyes (60%) during follow-up of 10±7 months. Nine eyes (30%) with previous latency defects improved in at least one check test, five of which normalised completely. Worsening was evident in seven eyes (23%), and three previously normal eyes developed new pathological latencies. P100 latencies in 14 eyes (47%) remained unchanged. Conclusion: After decompression surgery, DON remission was observed in all patients regarding vision and VECP amplitudes. New or persistent P100 latency defects were seen in 60% of eyes after surgery. DON is considered to be caused by compressive ischaemic damage, which further underlines the importance of early decompression surgery.